Lifecycle Completion and Reproductive Improvement of Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae), Following a Prey Shift Routine During Larval Development - Muhammad Waleed Shakoor; Jawwad Hassan Mirza; Muhammad Kamran; Fahad Jaber Alatawi (Biology)
The present study aimed to assess the lifecycle completion and reproductive improvement of green lacewing, Chrysoperla carnea (Stephens), larval instars in a prey shift routine while alternatively feeding on motiles of two-spotted spider mite, Tetranychus urticae Koch (natural prey), and the eggs of almond moth, Ephestia cautella (Walker) (factitious prey). The results showed that C. carnea larvae successfully completed their lifecycle and life span in the treatments where either the 2nd (T2) or 3rd (T3) instar larvae were fed with the eggs of E. cautella while other instars were provided with motiles of T. urticae, i.e., 1st–3rd and 1st–2nd, respectively. The predator larvae failed to transform from pupae to adults when only the 1st instar larvae were fed on the E. cautella eggs (T1). Similar results were found when all predator instars were reared on the motiles of T. urticae (T4). The shortest mean total larval duration and preoviposition period, the highest fecundity and fertility, and balanced sex ratio were recorded when 3rd instar larvae were fed only on E. cautella eggs (T3). The longest adult longevity and oviposition period were recorded when only the 2nd instar larvae were fed on E. cautella eggs (T2). The findings of the present study would be helpful in developing a self-sustained mite biological control strategy using C. carnea and provide a roadmap for future studies to elucidate the larval release efficiency of C. carnea with the supplementary diet for the management of greenhouse mite pests.